Joint association of weight-adjusted waist index and serum cotinine levels with systemic inflammatory index in adults - Yican Wang; Wanting He; Yong Zhou; Xiaoqiang Qiu; Qian Liao; Peng Tang (BMC Public Health)
Abstract Background Systemic immune inflammation index (SII) and systemic inflammation response index (SIRI) have recently emerged as more comprehensive indicators of systemic inflammation. However, few studies have been conducted to evaluate the effect of serum cotinine levels and weight-adjusted waist index (WWI) with SII and SIRI. This study aims to evaluate the independent and combined impact of serum cotinine levels and WWI with SII and SIRI. Methods This study enrolled 9,099 adults based on the National Health and Nutrition Examination Survey 2013–2016. Generalized linear models were employed to assess the associations between cotinine exposure and WWI with SII and SIRI. Moreover, smoothing curve fitting was conducted to investigate the potential nonlinear relationships between the WWI with SII and SIRI levels. Additionally, subgroup analyses and interaction tests were conducted. The combined associations of the WWI and cotinine with systemic inflammatory indices were further assessed. Results High serum cotinine exposure was associated with increased SII and SIRI. The WWI was positively correlated with SII and SIRI. Smoothing curve fitting demonstrated a nonlinearly increasing dose-response connection between WWI and SII and SIRI. Stratified analyses also showed a positive association of cotinine levels and WWI with the systemic inflammatory indices across subgroups. Furthermore, a positive joint association was observed between serum cotinine level and WWI with SII and SIRI. Conclusions These findings suggest that serum cotinine levels and WWI may be positively related to SII and SIRI. Serum cotinine levels and WWI may have a positive combined effect.